PENGARUH PERSONAL KONSELING TERHADAP PENGETAHUAN PENTINGNYA MENGIKUTI POSYANDU LANSIA DI DESA BULUMARGI KECAMATAN BABAT KABUPATEN LAMONGAN - Aris, Arifal; Susanti , Inta; Sari , Putri Mimika; Anisah , Isnin Hidayati; Triandika, Rendy Wahyu; Maulana, M Asrof (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Elderly Posyandu is a service vehicle for the elderly, the lack of knowledge of the elderly about the importance of attending the elderly Posyandu is one of the factors for the elderly not to attend the Posyandu, the elderly must attend the Posyandu because it can improve health status. The purpose of this study was to determine the effect of personal counseling on the knowledge of the elderly about the importance of joining the elderly Posyandu in Bulumargi Village, Bulumargi District, Lamongan Regency. The research design used a pre-experimental model with a pre-test-post- test approach. The sample for this study were 67 elderly respondents in Bulumargi Village, which consisted of 5 hamlets, using the Cluster Random Sampling Technique. Data were collected using a knowledge questionnaire, data were analyzed using the Wilcoxon test with a significance level of p<0.05. The results of the study almost all the elderly (80.5%) had a good level of knowledge. The results of the data analysis were P=0.000 where P<0.005 so that H1 was accepted, which means that there is an effect of counseling on the importance of attending the elderly Posyandu in Bulumargi Village, Babat District, Lamongan Regency. Personal counseling can be a promotive effort to increase the knowledge of the elderly, this method is more effective than health counseling in general, because the elderly can be more focused when given information, and are free to ask whatever they want to ask, so they can more quickly increase the knowledge and interest of the elderly to attending posyandu every month.